Neonatal Lymphopenia Screening Is Important for Early Diagnosis of Severe Combined Immunodeficiency - Poyraz, Aykut; Cansever, Murat; Muderris, Ipek; Patiroglu, Turkan (American Journal of Perinatology, 2021)
Objective T-cell receptor excision circles are expensive for neonatal severe combined immunodeficiency screening in developing countries. We aimed to detect immunodeficiencies presenting with lymphopenia to enable screening in the general population and to improve awareness regarding lymphopenia among clinicians.Study Design This study was conducted prospectively. In all newborns included, complete blood count from umbilical cord blood samples was recorded. Absolute lymphopenia was defined as absolute lymphocyte count <3,000/mm3 in umbilical cord blood sample. Complete blood count was repeated at month 1 in cases found to have lymphopenia.Results Overall, 2,000 newborns were included in the study. Absolute lymphopenia was detected in 42 newborns (2.1%), while lymphocyte count was >3,000/mm3 in 1,958 newborns (97.9%). Two infants with persisted lymphopenia at the end of the first month; therefore, further evaluations such as lymphocyte subsets for severe combined immunodeficiency (SCID) were done. In the first infant, the lymphocyte subgroups were detected as compatible with T (−), B (−), natural killer cells (NK) (+) SCID phenotype RAG defect. Sanger sequencing revealed that NM_000448 c.2209C > T (p.R737C) homozygous mutation of RAG1 gene. In the other infant, the lymphocyte subgroups were found as considered with T (−), B (+) NK (−) SCID phenotype JAK3 defect. Both patients underwent hematopoietic stem cell transplantation from human leukocyte antigen-matched family member.Conclusion Absolute lymphopenia by complete blood count is a more simpler, relatively noninvasive and inexpensive screening methodfor detection of SCID in newborns compared with T-cell receptor excision circles technique.Key Points
Keywords: neonatal lymphopenia; severe combined immunodeficiency; RAG1 deficiency; JAK3 deficiency